ABIA South and Southeast Asian art and archaeology index - Raven, Ellen M.; Lasschuijt, Helga I. (Leiden : Brill, 2002)
Supplies annotated and indexed entries on publications in Asian and European languages relating to prehistory, (proto)historical archaeology, art history (including modern art), material culture, epigraphy, palaeography, numismatics and sigillography.
Keywords: Art, Southeast Asian -- Bibliography; Art, South Asian -- Bibliography; Archaeology -- Asia -- Bibliography